(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Currently available messenger ribonucleic acid (mRNA)-based vaccines against coronavirus disease (COVID-19) have been shown to be effective even in highly immunocompromised hosts, including patients with multiple myeloma. However, vaccination failure can be observed in all patient groups. METHODS: This prospective study longitudinally assessed the humoral and cellular responses to a third booster dose of BNT162b2 mRNA-based vaccine in patients with myeloma (n = 59) and healthy controls (n = 22) by measuring the levels of anti-spike (S) antibodies (electro-chemiluminescence immunoassay) including neutralising antibodies and specific T-cells (enzyme-linked immunospot assay) following booster administration. RESULTS: The third booster dose showed a high immunogenicity on the serological level among the patients with multiple myeloma (median anti-S level = 41 binding antibody units [BAUs]/ml pre-booster vs 3902 BAU/ml post-booster, p <0.001; increase in the median neutralising antibody level from 19.8% to 97%, p <0.0001). Four of five (80%) patients with a complete lack of any serological response (anti-S immunoglobulin level <0.8 BAU/ml) after two vaccine doses developed detectable anti-S antibodies after booster vaccination (median anti-S level = 88 BAU/ml post-booster). T-cell responses were largely preserved among the patients with multiple myeloma with no difference from the healthy controls following baseline vaccination (median spot-forming units [SFU]/106 of peripheral blood mononuclear cells = 193 vs 175, p = 0.711); these responses were augmented significantly after booster administration among the patients with multiple myeloma (median SFU/106 of peripheral blood mononuclear cells = 235 vs 443, p <0.001). However, the vaccination responses remained highly heterogeneous and diminished over time, with insufficient serological responses occurring even after booster vaccination in a few patients irrespective of the treatment intensity. CONCLUSIONS: Our data demonstrate improvements in humoral and cellular immunity following booster vaccination and support the assessment of the humoral vaccine response in patients with multiple myeloma until a threshold for protection against severe COVID-19 is validated. This strategy can allow the identification of patients who might benefit from additional protective measures (e.g. pre-exposure prophylaxis via passive immunisation).